Associations of vitamin D-related single nucleotide polymorphisms with post-stroke depression among ischemic stroke population - Sun, Dongren; Song, Mingyu; Zeng, Chang; Chen, Hengshu; Zhang, Jingyuan; Liu, Fan; Luo, Shihang; Liao, Qiao; Xiao, Yeqing; Xu, Weiye; Zeng, Danfeng; Tan, Zheren; et al. (Frontiers in Psychiatry, 2023)
Objective: To investigate the relationship between single nucleotide polymorphisms (SNPs) related to vitamin D (VitD) metabolism and post-stroke depression (PSD) in patients with ischemic stroke. Methods: A total of 210 patients with ischemic stroke were enrolled at the Department of Neurology in Xiangya Hospital, Central South University, from July 2019 to August 2021. SNPs in the VitD metabolic pathway (VDR, CYP2R1, CYP24A1, and CYP27B1) were genotyped using the SNPscanTM multiplex SNP typing kit. Demographic and clinical data were collected using a standardized questionnaire. Multiple genetic models including dominant, recessive, and over-dominant models were utilized to analyze the associations between SNPs and PSD. Results: In the dominant, recessive, and over-dominant models, no significant association was observed between the selected SNPs in the CYP24A1 and CYP2R1 genes and PSD. However, univariate and multivariate logistic regression analysis revealed that the CYP27B1 rs10877012 G/G genotype was associated with a decreased risk of PSD (OR: 0.41, 95% CI: 0.18-0.92, P = 0.030 and OR: 0.42, 95% CI: 0.18-0.98, P = 0.040, respectively). Furthermore, haplotype association analysis indicated that rs11568820-rs1544410-rs2228570-rs7975232-rs731236 CCGAA haplotype in the VDR gene was associated with a reduced risk of PSD (OR: 0.14, 95% CI: 0.03-0.65, P=0.010), whereas no significant association was observed between haplotypes in the CYP2R1 and CYP24A1 genes and PSD. Conclusion: Our findings suggest that the polymorphisms of VitD metabolic pathway genes VDR and CYP27B1 may be associated with PSD in patients with ischemic stroke.